Sistematización de una estrategia de información, educación y comunicación para prevención del síndrome metabólico en profesionales del área de la salud (2015)
ABSTRACT: An information, education and communication campaign (IEC) was carried out about the metabolic syndrome, for university professional of the health sector; it is derived from a research carried out in this population. Objective: Recognition of dynamics and learning created in the professionals who perform the “We are Health” campaign. Methodology: Systematization of the experience was carried out by the campaign performers; who have defined the guiding question, rebuilt the experience, made a critical reflection, and identified significant aspects in it that let to build and validate the categorical system. By means of focus groups the information was collected. Results: “Learning by doing of the IEC strategy” was identified as the main category, and as emphasized subcategories: the reflection about the IEC and education, the extension-research relationship, critical aspects of the execution and design of messages and materials. Conclusions: Although it is recognized that the IEC processes do not guarantee immediate changes in individual and collective practices, they contribute to know and discuss health related issues. It was critically reflected on the way as education for health is made, emphasizing the need to consider individual and contextual aspects that mediate on health decisions, and the recognition of the health care professional as an agent and subject of such decisions. Key words: deep frying, nutrients, foods, cooking, oil, food handling methods.